"Nós fizemos uma eleição...": regularidades e rememorações de erros pela lente da Rede Globo - Fabbri Junior, Duílio (2019)
This thesis brings as an analytical gesture a look at the errors and regularities of the discourse of Rede Globo, one of the largest communication media in the world. The corpus of analysis is the commemorative series for the 50 years of the broadcasting, exhibited in the Jornal Nacional in April 2015, with extension to the site Memória Globo. The general objectives were to investigate how the errors in coverage in the area of politics were constituted during the series' placement, as well as to identify and problematize the discursive characteristics of remembrance, celebration and memory in the official history constructed by the broadcaster. We sought to outline the discursive processes that support supposed apologies for two facts: the coverage of the manifestation by Diretas Já in 1984 and the edition of the debate between Fernando Collor de Melo and Luiz Inácio Lula da Silva, in 1989. In search of regularities and dispersions, the discourses of the Rede Globo about the error in on-line and off-line platforms were investigated. Such approaches were compared with coverage of the broadcaster in 2018, during the national majority elections. The theoretical-methodological body is Discourse Analysis, based on the discursive order of Michel Foucault, in dialogue with Michel Pêcheux and Franco-Brazilian authors. The analysis showed that Rede Globo uses the same strategies in the past and the present, tough with different effects, depending on the conditions of production and the material supports, repeating ways to excuse errors, considering the political and social effects of its performance and discourses put into circulation.